Răspuns :
[tex]\displaystyle{ \frac{\frac{x-1}{2} - \frac{1}{3}}{4} - \frac{\frac{x-2}{3} - \frac{1}{2}}{2} = \frac{1}{4} }[/tex]
- se inmulteste tot randul cu 4 ca sa scapam de fractii
[tex]\displaystyle{ \frac{x-1}{2} - \frac{1}{3} - 2 \cdot (\frac{x-2}{3} - \frac{1}{2}) = 1 }[/tex]
[tex]\displaystyle{ \frac{x-1}{2} - \frac{1}{3} - \frac{2\cdot(x-2)}{3} +1 = 1 }[/tex]
[tex]\displaystyle{ \frac{3x - 3 - 2}{6} - \frac{4\cdot(x-2)}{6} = 0 }[/tex]
[tex]\displaystyle{ 3x - 5 = 4x - 8 }[/tex]
[tex]\displaystyle{ -5 = x - 8 }[/tex]
[tex]\displaystyle{ x = 3 }[/tex]